Comparison of quality of obturation and post-operative pain using manual vs rotary files in primary teeth - A randomised clinical trial - S Divya; Ganesh Jeevanandan; S Sujatha; E M G Subramanian; Vignesh Ravindran (Wolters Kluwer Medknow Publications, 2019)
Introduction: Cleaning and shaping plays a very important role in success of root canal procedures. There are various instrumentation techniques available for root canal preparation. Recently, an exclusive rotary file for root canal preparation of primary teeth has been introduced. Aim of the Study: The aim of this in vivo study was to compare the quality of obturation and intensity, and duration of post-operative pain between two rotary file systems with manual files during the pulpectomy of primary molars. Materials and Methods: Forty five primary mandibular molars were included in this study, which was randomly allocated into one of the three experimental groups (n = 15). Group A: Instrumentation was done using Hand K-file; Group B: Instrumentation was done using Kedo-S rotary file system; and Group C: Instrumentation was done using K3 rotary file system. The quality of obturation was recorded as optimal, underfilled, or overfilled using standardized intraoral periapical radiographs. This study also evaluated the intensity and duration of postoperative pain at different time intervals: 6, 12, 24, 48, and 72 hours following the pulpectomy. Results: With respect to quality of obturation, less underfilling was noticed in Kedo-S rotary files (16.7%) followed by using K3 rotary files (33.3%) and hand K files (43.3%). Kedo-S file showed the least underfilled canals (16.7%) and comparatively more overfilled canals (26.6%) and it was statistically significant (P value of 0.001 and 0.002 respectively). On comparing the intensity and duration of postoperative pain among the three groups, there was no statistically significant difference between these groups (P > 0.05). Conclusion: Kedo-S pediatric rotary file system shows considerably better quality of obturation when compared to that of K3 rotary and hand K file systems without much of any significant difference in relevance to the post-operative pain.